Evaluation of the Family Hope Program (PKH) in Agats District, Asmat Regency - Siti Maimuna Tuduho; Nur Jalal; Fitriani Fitriani (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
The Family Hope Program (PKH) is a conditional cash assistance-based social protection policy aimed at reducing poverty and increasing access for poor families to education, health, and social welfare services. This study aims to evaluate the implementation of PKH in Agats District, Asmat Regency, and identify factors influencing its implementation. The study used a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. Research informants included the district head, PKH coordinator, PKH facilitator, and beneficiary families. Data were analyzed through data reduction, data presentation, and conclusion drawing, while program evaluation used William N. Dunn's six criteria, namely effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The results show that PKH in Agats District has contributed positively to meeting the basic needs of KPM, especially in the aspects of education, maternal health, and economic support for the elderly. However, program implementation has not been fully optimal due to still facing problems with data synchronization between DTKS, Dukcapil, and Dapodik, delays in aid disbursement, limited facilitators, geographical barriers, and low understanding of some communities regarding the program mechanism. This study recommends continuous data updating, capacity building of facilitators, strengthening of cross-institutional coordination, and socio-cultural approaches to ensure more targeted implementation of PKH in remote areas.